Paediatric Asthma associated with passive smoking and garbage burning: A case report from Kedah, Malaysia - Afrose, Tahmina; Yeou, Soo Chun; Xi, Loh Zhen; Fernandez, Kevin; Habib, Narin; Das, Suprava (Journal of Biomedical Sciences, 2019)
Background Combatting with childhood asthma is a global challenge. Exposure to allergens, air pollutants, tobacco smoke, cold air, viral infection, and family history, are the few major causative factors for asthma. An eleven years old boy from Kedah, Malaysia, had the first asthmatic attack at the age of eight. Possible causes behind the development of his asthmatic attack include passive smoking, environment pollutant created by open residential burning of rubbish practiced by his family members, repeated exposure to allergens such as pollen, house dust mite, animal dander, and eczema. The patient has been treated with inhaled salbutamol BP (100μg/day), oral montelukast Na (5 mg/day) and mometasone furoate (55mcg. once daily). In conclusion, episodes of asthmatic attacks were mainly correlated with passive smoking & burning garbages. Comprehensive approaches such as health education, avoidance of the allergen, cleaning, and maintaining these practices can prevent the development of this morbid illness.